Gender, Race, and Immigration: Aging and Economic Security in Canada - Preston, Valerie; Kim, Ann; Hudyma, Samantha; Mandell, Nancy; Luxton, Meg; Hemphill, Julia (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
A growing share of the population in Canada comprised of aging immigrants lacks the financial resources for a secure retirement. Disproportionately visible minorities, many foreign-born seniors, have limited access to income security programs, private pensions, and savings. We examine the resulting racialization of poverty among aging immigrants in Canada with particular attention to the effects of visible minority and immigrant status and gender. Our analysis of 2006 Canadian census information confirms that many aging immigrants struggle to achieve economic security, which allows for a stable and adequate standard of living. Foreign-born seniors are more likely than Canadian-born seniors to have incomes that fall below the low-income cutoff, one measure of poverty. The percentages of Canadian-born and immigrant men and women from different ethnoracial backgrounds who have low incomes also differ substantially. Immigrant women, particularly those who are visible minorities, are the most impoverished. We advocate an intersectional approach to understanding and addressing poverty among seniors. For aging immigrants, the chances of being impoverished depend on gender and ethnoracial background as well as on place of birth. Une part croissante de la population canadienne composée d’immigrants vieillissants ne dispose pas des ressources financières nécessaires pour s’assurer une retraite sereine. Une part disproportionnée des minorités visibles, de nombreux aînés nés à l’étranger, ont un accès limité aux programmes de sécurité du revenu, aux régimes de retraite privés et aux économies. Nous examinons ici la racialisation de la pauvreté qui en découle parmi les immigrants vieillissants du Canada, avec une attention particulière aux effets du genre et du statut de minorité visible ou d’immigrant. Notre analyse des renseignements issus du recensement canadien de 2006 confirme que de nombreux immigrants vieillissants doivent se battre pour obtenir la sécurité économique qui leur apporterait un niveau de vie stable et adéquat. Les aînés d’origine étrangère sont plus susceptibles que ceux d’origine canadienne d’avoir des revenus inférieurs au seuil de faible revenu, l’une des mesures de la pauvreté. Les pourcentages de Canadiens et de Canadiennes et d’immigrants hommes et femmes d’origines ethnoraciales différentes qui disposent de revenus faibles diffèrent aussi considérablement. Les immigrantes, et plus particulièrement celles issues des minorités visibles, sont les plus pauvres. Nous défendons une approche croisée pour comprendre le problème de la pauvreté parmi les aînés et y remédier. Pour les immigrants vieillissants, le risque de pauvreté dépend non seulement du sexe et de l’origine ethnoraciale, mais également du lieu de naissance.